Isolation and Characterization of Plant-Growth-Promoting Bacteria Associated with Salvinia auriculata Aublet - Jussara Tamires de Souza Silva Goulart; Gabriel Quintanilha-Peixoto; Bruno dos Santos Esteves; Suzane Ariadina de Souza; Pollyanna Santiago Lopes; Nathália Duarte da Silva; Julia Ribeiro Soares; Laura Mathias Barroso; Marina Satika Suzuki; Aline Chaves Intorne (Microorganisms)
Salvinia auriculata Aublet is a floating aquatic plant, capable of absorbing the excess of nutrients and water contaminants and can be used in effluent treatment plants. The ability to survive in degraded areas may be related to the association with beneficial bacteria capable of promoting plant growth. However, little is known about the microbiota associated with this aquatic plant and its potential application to the aquatic environment. In this sense, this work aims to identify bacteria associated with S. auriculata that could be able to promote plant growth. Eighteen bacterial strains were identified by sequencing of the 16S rRNA gene, belonging to the genera Agrobacterium, Bacillus, Curtobacterium, Enterobacter, Pseudomonas, Siccibacter, and Stenotrophomonas. All isolates produced indole compounds, 12 fixed N2, and 16 solubilized phosphate. A new strain of Enterobacter (sp 3.1.3.0.X.18) was selected for inoculation into S. auriculata. For this purpose, 500 mL of nutrient solution and 1 g of the plant were used in the control and inoculated conditions. Enterobacter inoculation promoted a significant increase (p ≤ 0.05) in fresh plant biomass (17%) after 4 days of cultivation. In summary, the present study characterized 18 plant-growth-promoting bacteria isolated from S. auriculata with potential for biotechnological application, such as the production of bioinoculants or biomass resources, to protect or improve plant growth under conditions of stress.